2018
DOI: 10.1103/physrevb.97.165430
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kekulé adatom ordering due to strain in graphene

Abstract: Intervalley scattering of carriers in graphene at "top" adatoms may give rise to a hidden Kekulé ordering pattern in the adatom positions. This ordering is the result of a rapid modulation in the electron-mediated interaction between adatoms at the wave vector K − K , which has been shown experimentally and theoretically to dominate their spatial distribution. Here we show that the adatom interaction is extremely sensitive to strain in the supporting graphene, which leads to a characteristic spatial modulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Soon after, Gamayun et al 22 studied theoretically the low energy band dispersion laws of the Kek-Y distorted graphene finding a gapless spectrum with valley-momentum locking for the charge carriers. Other recent theoretical studies of the Kek-Y phase in graphene describe its effects on Klein tunneling 32 , its interplay with mechanical strain 33,34 and the formation of multiflavor Dirac Fermions in Kekulé-textured graphene bilayers 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, Gamayun et al 22 studied theoretically the low energy band dispersion laws of the Kek-Y distorted graphene finding a gapless spectrum with valley-momentum locking for the charge carriers. Other recent theoretical studies of the Kek-Y phase in graphene describe its effects on Klein tunneling 32 , its interplay with mechanical strain 33,34 and the formation of multiflavor Dirac Fermions in Kekulé-textured graphene bilayers 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, both couple asymmetrically with each valley by breaking the inversion symmetry while preserving time reversal. Nevertheless, strain offers the advantage of being tunable and it is in intimate relation with the kekulé phase, since this phase is expected to appear in the presence of uniaxial strain 10,47 . In general, uniaxial strain alters the band structure of graphene by (1) distorting the shape of the Brillouin zone, thus changing the geometrical position of the high symmetry points due to the modification of the lattice vectors 48 , and (2) moving the Dirac cones away from the high symmetry points, since it changes unevenly the three hopping energies connecting neighboring sites 49 .…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of both the Kekulé distortions on the electronic and transport properties of graphene have been widely explored, for instance: Wang et al investigated the enhanced valley-dependent Klein tunneling of electrons through a rectangular potential barrier in Kek-Y graphene 9 ; Beenakker et al showed that a potential with a Kekulé modulation can generate pseudo-Andreev reflections, where incoming electrons in a certain valley are reflected in the other 10 ; the nature of valley-dependent currents in Kek-O distorted superconducting heterojunction was recently explored by Wang et al 11 ; also, recent studies by Andrade et al found, and later confirmed experimentally by Eom and Koo 1 , that the uniaxial strain in Kek-Y graphene can separate the Dirac cones away from the Γ-point 12,13 . Other studies include the proposal of a device to control the valley orientation of channel electrons based on the valley precession produced by the Kek-Y texture 14 , as well as the study of the resonant electronic transport in graphene nanoribbons with periodic Kekulé distortions 15 .…”
Section: Introductionmentioning
confidence: 93%